2018
DOI: 10.3329/cmoshmcj.v16i2.37288
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Immunochromatographic Test for Antibody in Diagnosis of Typhoid Fever in Children Admitted in A Tertiary Care Hospital

Abstract: Background: To determine the Validity of Immunochromatographic Test (ICT) in diagnosis of typhoid fever in children admitted in a tertiary care hospital. Methods: This cross sectional study was carried out the in Pediatric & Medicine wards of Chittagong Medical College Hospital (CMCH), Chittagong during the period July 2012 to June 2013. A total number of 150 clinically suspected cases of typhoid fever (Age >6 months to18 years) were enrolled in this study. After taking informed written consent, detailed histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
1
0
2
Order By: Relevance
“…They suggested that rather than using Widal test it might be more useful to use rapid test like Typhi-dot in routine diagnostic service besides blood culture. Studies from Bangladesh reported similar rate of sensitivity and specificity of a rapid ICT (SD Bioline) and TUBEX® for the diagnosis of typhoid fever [45,46]. This is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They suggested that rather than using Widal test it might be more useful to use rapid test like Typhi-dot in routine diagnostic service besides blood culture. Studies from Bangladesh reported similar rate of sensitivity and specificity of a rapid ICT (SD Bioline) and TUBEX® for the diagnosis of typhoid fever [45,46]. This is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Only IgM (early phase) or both IgM and IgG positive (middle phase) indicates current infection and IgG without IgM usually denotes past, reinfection or late stage disease when sero-conversion has already been occurred. In this study we observed the percentages of IgG positive cases among culture positive group was high, but in other studies conducted through different ICT kit found more IgM positive cases [45]. This could be explained by the disappearance of IgM in the late stage of disease or masking of IgM by IgG [50].…”
Section: Discussioncontrasting
confidence: 53%
“…Similar study from Pakistan was observed where 55.2% were positive by ICT 17 . In contrast to our study, another study from Bangladesh found only 24.7% 18 .…”
Section: Figures In Parenthesis Indicate Percentage (P Value=0000003743 P <005 By Chi-square Test) Discussioncontrasting
confidence: 99%